2000
DOI: 10.1046/j.1440-6047.2000.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Food intakes and habits of rural elderly Malays

Abstract: A cross-sectional nutritional survey was carried out on 350 elderly Malays aged 60 and above from 11 randomly selected villages in a rural area on the east coast of Malaysia. The findings indicated that the mean intakes of energy and of all of the nutrients investigated were below the Malaysian Recommended Dietary Allowances, except for protein and vitamin C. With respect to dietary habits, almost all of the subjects reported that they had breakfast (99.3%), lunch (97.9%) and dinner (90.4%) daily or almost dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
6
39
0
Order By: Relevance
“…Therefore, a large proportion of residents in these shelter homes, originated from rural villages, were poorly educated and at-risk of undernutrition. The results of this study are supported by those by Shahar et al who also found that rural Malaysians were at high risk of undernutrition (39%) and unemployment with no steady financial support (60%) and were also often uneducated (48%) (Shahar et al, 2001). Interestingly, far fewer older people in this study had BMIs o18.5 kg/m 2 than in the study by Suzana et al (14.30 vs 38.5%) (Suzana et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, a large proportion of residents in these shelter homes, originated from rural villages, were poorly educated and at-risk of undernutrition. The results of this study are supported by those by Shahar et al who also found that rural Malaysians were at high risk of undernutrition (39%) and unemployment with no steady financial support (60%) and were also often uneducated (48%) (Shahar et al, 2001). Interestingly, far fewer older people in this study had BMIs o18.5 kg/m 2 than in the study by Suzana et al (14.30 vs 38.5%) (Suzana et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…Elderly consider satisfaction with social relationships and participation in community and voluntary work and spending time with family members as positive experiences in ageing [11,22,24,25]. Lack of meaningful social contacts lead to withdrawal from social community [8].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological, social and physical needs of the elderly are met when they live with family members. Majority of the elderly in Malaysia like their counterpart in Asia live with their children and a study conducted in Malaysia has shown that life satisfaction of the older adults can predict the living arrangement directly or indirectly though social support [25,34]. Being cognizant of the importance of living with family members and the changes in the family structure in Malaysia, the Malaysian government's objective is to allow the elderly to live in their own homes and in their communities and being cared for by their families, neighbours and communities [35].…”
Section: Social Support Variables Mobilitymentioning
confidence: 99%
“…The manifestations of metabolic syndrome are high cholesterol and triglyceride levels and central obesity with the majority reported with antecedents of cardiovascular diseases.Metabolic syndrome represents a public health problem due to severe multisystem consequences it induces, affecting a large group of people especially older population (Ciucurel & Iconaru., 2012). In contrary to Shahar et al (2001)'s finding, the major chronic illness reported among the elderly were joint pains (45.0%). This discrepancy was due to joint pains were considered as symptoms not as a disorder as osteoarthritis.…”
Section: Resultsmentioning
confidence: 58%
“…Most of the elderly had one illness while a smaller percentage had two or three diseases. About 60.1 % had been diagnosed with chronic diseases with a smaller percentage had two or three illnesses (Shahar et al, 2001). Most of these women have hypertension (68.43%) followed by diabetes mellitus (47.74%), osteoarthritis (21.93%) and other medical disorders.…”
Section: Resultsmentioning
confidence: 99%